Relationship between polymeric foam characteristics and properties of porous bone substitute fabricated by polymeric foam replication - Wattanutchariya,W. (2015)
© 2013 IEEE. Polymeric foam replication is one technique used to produce bone scaffold for porous bone substitution or bone grafting in the human body. This method provides scaffolds similar to trabecular bone, as well as producing a controllable pore size and porosity scaffold. Preliminary studies illustrated that the characteristics of polymeric foam such as pore size and porosity could affect both physical and mechanical properties of the resulting scaffold. Therefore, the objective of this study is to evaluate the relationship of polymeric foam characteristics with the properties of the porous bone scaffold. In this study, 5 different types of polymeric foam were evaluated, and the phosphate glass was implemented as the biomaterial slurry. Scaffold forming took place by immersing the foam types into the slurry and then sintering them at 750C for 3 hours. Porosity and compression testings were then used to analyze the physical and mechanical properties of the specimens. Results indicate that the optimal condition of both physical and mechanical properties was found when the polymeric foam with the highest pore density (99.5%) and approximately 300 μm pore size range was used. However, the highest compression strength obtained was only 3.48 MPa, which is at the lower range of the trabecular bone's mechanical properties. Future study will therefore focus on producing stronger porous bone scaffold for porous bone substitution.